Addressing the Teen Mom Situation in Thailand: A Systematic Review on Challenges, Initiatives and Recommendations for Improvement - Jukkrit Wungrath; Phinphot Phrommasen; Wanchalerm Ritthimon (Jurnal Keperawatan Indonesia)
Teenage pregnancy in Thailand poses significant public health challenges with implications for societal welfare and economic development. This systematic review analyzed the challenges faced by teenage mothers in Thailand, evaluated existing initiatives, and proposed evidence-based recommendations. A comprehensive literature search was conducted using the Scopus and Web of Science databases and others focusing on literature from 2016 to 2023. Keywords included “teenage pregnancy,” “teen mom,” “unwanted pregnancy,” and “unintended pregnancy” resulting in the selection of 36 studies. The PRISMA framework was followed to ensure a systematic approach. Data extraction focused on societal, educational, economic, and health-related challenges as well as the effectiveness of current interventions. Results indicated that teenage mothers in Thailand face substantial societal stigma, educational disruptions, economic difficulties, and significant health risks. Current initiatives and policies are insufficient in coverage and effectiveness. This review highlights the need for comprehensive sex education, improved access to contraception, youth-friendly sexual and reproductive health services, and targeted support programs for teenage mothers, emphasizing a multi-sectoral approach involving government agencies, Non-Governmental Organizations (NGOs), educational institutions, healthcare providers, and communities. The findings suggest that better-targeted interventions and collaborative efforts are required to reduce teenage pregnancy and improve the quality of life for teenage mothers in Thailand to foster a healthier and more inclusive society.